The influence of psychological empowerment of organisational commitment among nurses. - Adibah Amin Kruti (2015)
This study examines the relationship between empowerment (self- determination, meaningful, impact, and competence) on organisational commitment.Positive correlation were found between meaningful, self-determination, and impact on organisational commitment.